PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN ABAH BURGER DAHLIA PEKANBARU - Rista Firdianti; Okta Karneli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research was conducted at the dahliah Pekanbaru burger located on Jl. Dahlia No.24 sukajadi, kec. Sukajadi, the city of Pekanbaru - Riau. The problem in this study is the decline in the past year and not achieving the target number of customers who are allegedly influenced by customer loyalty. The purpose of this study was to determine the effect of service quality and product quality on customer loyalty Abah Dahlia burger Pekanbaru. Samples were taken based on the method using the Slovin formula, amounting to 100 respondents.Hypothesis testing uses simple linear regression analysis methods and multiple linear regression analysis with the results showing that service quality and product quality significantly influence customer loyalty. With a simple linear regression calculation of the coefficient of determination (R2) the quality of service to customer loyalty is obtained R Square of 0, 440 or 44.0%, product quality to customer loyalty obtained R Square of 0, 430 or 43.0% and the calculation of multiple linear regression coefficient of determination (R2) service quality and product quality on customer loyalty obtained R Square of 0, 496 or 49.6%. This shows the quality of service and product quality gives an effect of 49.6% on customer loyalty Abah dahliah burger Pekanbaru. Keywords: Service Quality, Product Quality, Customer Loyalty.